Hydrophilicity enhancement of metal oxide nanoparticles incorporated polysulfone ultrafiltration membrane - N. S. M., Sabri; H., Hasbullah; N., Said; N., Ibrahim; R. M., Kasmani; R. R., Ali; Sunarti, Abd Rahman (Universiti Teknologi Malaysia, 2017)
Hydrophilicity property of membrane is a crucial feature in preventing fouling by most organic components including proteins. In this work, two different metal oxide nanoparticles were selected and their effects on hydrophilicity of polysulfone (PSf) flat sheet membrane for ultrafiltration were investigated. Addition of copper oxide (CuO) and iron oxide (Fe2O3) of 0.25 wt% concentration in N-methyl-2-pyrrolidone (NMP) were also compared to a neat PSf membrane. The membranes were prepared via dry-wet phase inversion technique with 18 wt% of PSf with 5 wt% polyvinylpyrrolidone (PVP). The physical and chemical properties of the prepared membranes were observed by contact angle measurements, porosity, average pore size and scanning electron microscope (SEM). The membranes permeation performance was also examined in term of pure water flux (PWF) and protein rejection by using bovine serum albumin (BSA) solution. Contact angle value of CuO/PSf obtained was 67.1° that was lower than the neat PSf membrane of 87.9° whereas 68.1° for Fe2O3/PSf indicating that metal oxides addition did enhance the membrane hydrophilicity with CuO was slightly better than Fe2O3. The reduction in contact angle ensured that the pure water flux through the membrane with metal oxide additive would improve as well. For CuO, the PWF increased to 159.3 Lm2hr-1 from 81.3 Lm-2hr-1 of neat PSf, while Fe2O3 showed the PWF at 93.4 Lm-2hr-1 . Morphological analyses displayed asymmetric membranes with narrow finger-like structure were formed in this study. A well-formed dense top layer indicated that the membrane would possess good BSA rejection property with 92% of rejection achieved by CuO/PSf membrane. The incorporation of nanoparticles with the membrane is proven to be an effective mean to increase the membrane hydrophilicity with improved water flux and BSA rejection.